Learning path : Red Hat Certified System Administrator (RHCSA) - Vugt, Sander van; Safari eBooks ([Place of publication not identified] : Pearson, 2016)
"Learn solid fundamental Linux operating system skills with Beginning Linux System Administration LiveLessons. Taught by best-selling author and trainer Sander van Vugt, Beginning Linux System Administration LiveLessons walks you through the essential system administration tasks you need to know to get up and running in Linux quickly. This 12 lesson video course starts with the basics, from determining which distribution is right for you to walking through the steps of installing Linux on the two most popular flavors: Ubuntu and Red Hat. Next, you will connect to Linux and really get your feet wet, using an editor and working with files. You will then dive into managing permissions, processes and software before working with logs, exploring Linux security and finally managing services."--Resource description page.
Beginning Linux system administration LiveLessons / Sander van Vugt -- Red Hat Certified System Administrator complete video course / Sander van Vugt -- Red Hat Certified System Administrator (RHCSA) exam prep video workshop / Sander van Vugt -- Red Hat Certified System Administrator (RHCSA) in Red Hat OpenStack / Sander van Vugt.
Title from resource description page (viewed July 28, 2016).
Presenter, Sander van Vugt.
Keywords: Linux; Operating systems (Computers); Open source software; Electronic books